PERAN KONSELOR ADIKSI DALAM MENANGANI PECANDU NARKOBA DI YAYASAN KELOMPOK PEDULI PENYALAHGUNAAN NARKOTIKA DAN OBAT-OBATAN TERLARANG (YKP2N) MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study discusses the  Addiction Counselor in dealing with Drug Addicts at the Foundation for the Concern for the Abuse of Narcotics and Drugs (YKP2N) Makassar. This study used a descriptive qualitative research type located at the Office of the Foundation for the Concern for the Abuse of Narcotics and Drugs (YKP2N) Makassar. The research approach used is the Islamic counseling and counseling approach and the psychological approach. The results showed that the efforts made by addiction counselors in dealing with drug addicts were divided into 5 (five) parts, namely: conducting assistance, conducting assessments, conducting monitoring, conducting home visits, and conducting counseling. The obstacles faced by addiction counselors in dealing with drug addicts are as follows: lack of self-acceptance for drug addicts clients, low levels of education, lack of time discipline, and limitations of counselors in counseling science.